Global aspects and cultural perspectives on knowledge management : emerging dimensions - Jennex, Murray E., 1956- (Hershey, PA : Information Science Reference, 2011)
'This book presents new technologies, approaches, issues, solutions, and cases that can help an organization implement a knowledge management (KM) initiative, presenting issues that drive the technologies, processes, methodologies, techniques, and practices used to implement KM in a variety of ways and in the multi-faceted modern environment that we find ourselves in today'--Provided by publisher.
Includes bibliographical references (p. 376-419) and index.
Keywords: Knowledge management